Simulasi dan Studi Eksperimen Defleksi Beam Bright Mild Steel Akibat Variasi Beban Horisontal - Putra Negara, Dewa Ngakan Ketut; Gunawan Tista, Si Putu Gde (Jurnal Energi Dan Manufaktur; Vol 5, No.1 April 2011, 2012)
Beam is a structural member whose cross-sectional dimensions are relatively smaller than its length. Beams play significantroles in many engineering applications, including buildings, bridges, automobiles, and airplane structures. Beams arecommonly subjected to transverse loading, which is a type of loading that creates bending in the beam. In designing of amachine component or structure, deflection has an important role to be considered. If deflection occurred exceeds limitallowed, it can affect serious hazard on machine elements or structure due to it can affect of component deviate from its mainfunction. In this research, material to be used was Bright Mild Steel (ASTM 1060), with specimen in the form of portal beam.Physical condition of beam was modeled use of BEAM3 2D. Variation of loads to be applied were W = 100, 150, 200, 250,300, 350, 400, 450, 500, and 550 gr and concentrated in the one of portal in vehorizontal direction. The result of simulationwas verificated by experimental data. Evaluation was carried out by statistical test (t-test). The result of simulation iscategorized to be good if the result of simulation is same with experimental data. The result of research shows thatloading has a significant effect on the deflection. The higher load affect the higher of deflection Modeling use of BEAM3 2Dgave good result of deflection. This is showed from t-test have done, where the result of simulation was same withexperimental data.
Keywords: computer simulation, deflection, beam.